Transformation in contribution of Teacher Educators in implementation of NEP 2020: The Changing Role of Teacher Educators in Implementing NEP 2020 (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Any country's ability to develop depends on the calibre of its teachers, and education is the keyto that.The components responsible for effective instruction and student accomplishment are teachers'expertise, commitment, competence, professionalism, and motivation. Nowadays, producing suchinstructors is a significant task for governments all around the world.A teacher's job has become increasingly difficult in light of new educational and psychological theories,philosophy, sociology, and globalisation due to the ever-growing body of knowledge availabletoday.Today, The educational programmes must be well thought out and creative and must beexamined, analysed, reformed, rethought about, and reoriented. One of the key aims of the Indiangovernment is to promote quality and excellence in education.The Indian government has beenconcentrating on quality and excellence in education at all levels in order to attain the goal of improvedquality at all educational levels.The current study focuses on how teacher educators' roles are altering in light of NEP2020. It alsoemphasises the many tasks that instructors are desired to play in classrooms under NEP2020. Thestudy offered solutions to the problems that teacher education faces. This essay is analytical in style.The usage of pertinent books, articles, and other research papers has been made. According to theneeds of the study, data and information have been gathered from relevant sources. In this investigation,an interpretive methodology was used. Teacher education=Teaching skills + pedagogical theory+professional skills.‟ Clinton stated for American Education in the 21st Century (1996) that, “Every class musthave hardworking and responsible personality”.